The impact of race/ethnicity on pancreaticoduodenectomy outcomes for pancreatic cancer. Issue 1 (30th September 2022) - Alwatari, Yahya; Mosquera, Catalina M.; Khoraki, Jad; Rustom, Salem; Wall, Natalie; Sevdalis, Athanasios E.; Stover, Weston; Trevino, Jose G.; Kaplan, Brian
Abstract: Purpose: To investigate the impact of race/ethnicity on surgical outcomes following pancreaticoduodenectomy for pancreatic cancer. Methods: A retrospective review of patients undergoing pancreaticoduodenectomy for adenocarcinoma in the National Surgical Quality Improvement Program (NSQIP) database from 2014 to 2019. Patient and tumor characteristics and 30‐day postoperative outcomes were compared. Multivariable logistic and linear regression models were conducted to investigate the relationship between race/ethnicity and surgical outcomes. Results: Six thousand five hundred and sixty‐two patients were included (84.5% White, 7.9% Black, 3% Hispanic, 4.6% Asian). Larger proportions of Blacks had preoperative American Society of Anesthesiologists class 3 or 4. There were no significant differences in tumor characteristics or operative techniques. A smaller proportion of Asians and Hispanics received neoadjuvant chemotherapy and/or radiation than Blacks and Whites. Relative to White, the Black race was independently associated with postoperative sepsis and reoperation. Both Black and Hispanic race/ethnicity were associated with prolonged intubation and delayed gastric emptying, and minorities races/ethnicities were associated with longer length of hospital stay. Relative to White, Hispanic, and Asian race/ethnicity were independently associated with a lower likelihood of neoadjuvant therapy (NAT) receipt. Conclusion: In ACS‐NSQIP participating hospitals, non‐White race/ethnicity was independently associated with adverse outcomes after pancreatic cancer resection. A possible disparity in NAT receipt may exist in Asian and Hispanic patients undergoing surgical resection.